Reversible molecular pathology of skeletal muscle in spinal muscular atrophy. - Mutsaers, C; Wishart, T; Lamont, D; Riessland, M; Schreml, J; Comley, L; Murray, L; Parson, S; Lochmüller, H; Wirth, B; Talbot, K; Gillingwater, T (2011)
Low levels of full-length survival motor neuron (SMN) protein cause the motor neuron disease, spinal muscular atrophy (SMA). Although motor neurons undoubtedly contribute directly to SMA pathogenesis, the role of muscle is less clear. We demonstrate significant disruption to the molecular composition of skeletal muscle in pre-symptomatic severe SMA mice, in the absence of any detectable degenerative changes in lower motor neurons and with a molecular profile distinct from that of denervated muscle. Functional cluster analysis of proteomic data and phospho-histone H2AX labelling of DNA damage revealed increased activity of cell death pathways in SMA muscle. Robust upregulation of voltage-dependent anion-selective channel protein 2 (Vdac2) and downregulation of parvalbumin in severe SMA mice was confirmed in a milder SMA mouse model and in human patient muscle biopsies. Molecular pathology of skeletal muscle was ameliorated in mice treated with the FDA-approved histone deacetylase inhibitor, suberoylanilide hydroxamic acid. We conclude that intrinsic pathology of skeletal muscle is an important and reversible event in SMA and also suggest that muscle proteins have the potential to act as novel biomarkers in SMA.